2003
DOI: 10.1111/j.0909-8836.2003.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

On permeability of methyl methacrylate, 2‐hydroxyethyl methacrylate and triethyleneglycol dimethacrylate through protective gloves in dentistry

Abstract: Continuous glove use is more common in dentistry than in most other occupations, and the glove should offer protection against blood-borne infections, skin irritants and contact allergens. Methacrylate monomers are potent contact allergens, and it is known that these substances may penetrate the glove materials commonly used. The aim of this study was to assess the permeability of various types of gloves to methyl methacrylate (MMA), 2-hydroxyethyl methacrylate (HEMA) and triethyleneglycol dimethacrylate (TEGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 26 publications
1
41
0
3
Order By: Relevance
“…[13][14][15][16] Methyl methacrylate, as a small molecular acrylate, can permeate thin protective disposable gloves; protective gloves are insufficient due to the permeability of natural rubber latex and vinyl gloves to these substances. [17][18][19][20][21] With the growing evolution of cosmetic dentistry, which exposes dental workers to resins, bleaches and adhesives, composed of acrylic-and methacrylic-based materials that can cause hand eczema, more dentists are exposed to methyl methacrylate. 3,5 Previous studies in Serbia 17 and in Valencia, Spain, 22 reported that 5-25% of dental personnel might be sensitized to methyl methacrylate, while our study revealed that 2.5% (n = 8) developed this type of allergy.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Methyl methacrylate, as a small molecular acrylate, can permeate thin protective disposable gloves; protective gloves are insufficient due to the permeability of natural rubber latex and vinyl gloves to these substances. [17][18][19][20][21] With the growing evolution of cosmetic dentistry, which exposes dental workers to resins, bleaches and adhesives, composed of acrylic-and methacrylic-based materials that can cause hand eczema, more dentists are exposed to methyl methacrylate. 3,5 Previous studies in Serbia 17 and in Valencia, Spain, 22 reported that 5-25% of dental personnel might be sensitized to methyl methacrylate, while our study revealed that 2.5% (n = 8) developed this type of allergy.…”
Section: Discussionmentioning
confidence: 99%
“…The causative chemical of case 2 was MMA, though she was wearing natural or nitrile rubber gloves. Dentistry workers often wear gloves when using dental acrylic materials, but many affected workers do not predict that acrylic monomer can penetrate the disposable gloves usually used, which are made by natural rubber, polyvinyl chloride, or nitrile rubber, and cause ACD, as in case 2 12) . Such cases have been reported in Japan and the U.S. 13,14) Besides acrylates, additives in dental plastics such as initiators, accelerators, catalysts, inhibitors, pigments, and various rubber chemicals cause ACD in dental personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Case 2 could free herself of her symptoms by changing her nitrile rubber gloves immediately after they became contaminated with a (meth)acrylate monomer. (Meth)acrylates easily penetrate through disposable gloves 12) . If a sensitized patient is told that disposable gloves cannot protect skin from acrylic products, he/she can frequently change contaminated gloves to prevent ACD.…”
Section: Discussionmentioning
confidence: 99%
“…The glove material most frequently used was PVC, which is gratifying, considering the possible side-effects of natural rubber latex (20). Protection against MA is similar for PVC, natural rubber latex, and nitrile rubber and unfortunately lasts only for a few minutes (17,18). This short protection time implies that a frequent change of gloves is necessary to achieve proper skin protection.…”
Section: Discussionmentioning
confidence: 99%
“…Since protective gloves are permeable to MA, there are obvious problems involved in protecting the skin (17,18). Besides gloves can be considered to obstruct the work.…”
mentioning
confidence: 99%